Hydrogen Peroxide–Producing Lactobacilli Are Associated With Lower Levels of Vaginal Interleukin-1β, Independent of Bacterial Vaginosis. Issue 7 (July 2015) - Mitchell, Caroline; Fredricks, David; Agnew, Kathy; Hitti, Jane
Abstract : Background: The presence of hydrogen peroxide (H2 O2 )–producing lactobacilli in the vagina is associated with decreased rates of preterm birth and HIV acquisition. We hypothesize that this is due to immunomodulatory effects of these species. Methods: Concentrations of interleukin (IL)-1β, IL-6, IL-8, secretory leukocyte protease inhibitor, and human β-defensin 2 were quantified from vaginal swabs from 4 groups of women: women with and without bacterial vaginosis (BV) by Nugent score, further stratified by detection of H2 O2 -producing lactobacilli by semiquantitative culture. Ten quantitative polymerase chain reaction assays characterized the presence and quantity of select Lactobacillus and BV-associated species in each group. Levels of immune markers and bacteria were compared between the 4 groups using analysis of variance, Kruskal-Wallis, Mann-Whitney U, or χ 2 tests. Results: Swabs from 110 women from 4 groups were included: 26 had a normal Nugent score (BV−), and no H2 O2 -producing lactobacilli detected (H2 O2 −); 47 were BV−, H2 O2 +; 27 BV+, H2 O2 −; and 10 BV+, H2 O2 +. The groups were similar in age, marital status, and reproductive history, but not ethnicity: the BV−, H2 O2 − group had more white participants ( P = 0.02). In women with and without BV, IL-1β was lower in the H2 O2 + groups. Human β-defensin 2 was lowest in BV+ H2 O2 − women and highest in BV−, H2 O2 −. Secretory leukocyte protease inhibitor was lower in women with BV and did not differ by the presence of H2 O2 -producing lactobacilli. In regression analysis, higher quantities of Lactobacillus crispatus were associated with lower quantities of IL-1β. Detection and quantity of BV-associated species by quantitative polymerase chain reaction was significantly different between women with and without BV, but not between women with and without H2 O2 -producing lactobacilli within those groups. Conclusions: The presence of H2 O2 -producing lactobacilli is associated with lower levels of some vaginal proinflammatory cytokines, even in women with BV. Abstract : The presence of H2 O2 -producing lactobacilli is associated with lower levels of vaginal proinflammatory cytokines, even in women with bacterial vaginosis.